Effect of regrouping unfamiliar pigs at weaning on immune function - Frank Blecha; D S Pollmann; David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1983)
Pigs weaned at 3 weeks of age and regrouped with unfamiliar individuals had a 4-fold increase in plasma cortisol when compared to pigs that remained in a litter group. However, cellular measures of immune function were not altered by regrouping.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Weaning; Immunity